Expression of feline immunodeficiency virus gag and env precursor proteins in Spodoptera frugiperda cells and their use in immunodiagnosis. - Verschoor, E J (1993)
The gag and env genes of the feline immunodeficiency virus strain UT113 were cloned into a baculovirus transfer vector. The recombinant plasmids were used to create recombinant baculoviruses that expressed either the gag or the env precursor protein in insect cells (Sf9 cells). Leader sequence cleavage occurred in Sf9 cells expressing the envelope precursor, but further processing was not observed. Crude lysates of insect cells infected with the wild-type baculovirus or with the recombinant viruses were used to develop an enzyme-linked immunosorbent assay for the detection of feline immunodeficiency virus-specific antibodies in cat sera. The assay showed a higher sensitivity and specificity than immunofluorescence and Western blotting (immunoblotting).